Renoprotective effects of levosimendan on acute kidney injury following cardiac arrest via anti‐inflammation, anti‐apoptosis, and ERK activation. Issue 8 (12th July 2021) - Tian, Lei; Wang, Shiwei; Zhao, Li; Lu, Xiaoye; Zhu, Changqing; Gong, Hao; Yang, Weiqiang
Abstract : ATP‐sensitive potassium channels (KATPs) have protective effects in ischemia–reperfusion‐induced injuries and can be activated by levosimendan. This study investigated the effects of levosimendan on renal injury, inflammation, apoptosis, and survival in a rat model of acute kidney injury (AKI) following cardiac arrest (CA) and cardiopulmonary resuscitation (CPR). Rats underwent a 5‐min asphyxia‐based CA and resuscitation. The rats were treated with levosimendan after successful resuscitation. Renal functions, histological changes, inflammatory responses, and apoptosis were examined. NRK‐52E cells treated by hypoxia/reoxygenation (H/R) were used to establish an in vitro CA‐CPR model. Rats in the CA‐induced AKI group had a low survival rate and increased levels of creatinine, blood urea nitrogen, and proinflammatory cytokines, as well as increased tubular injury. These results were significantly reversed after treatment with levosimendan. Levosimendan downregulated the expression of the apoptosis‐related proteins Bax, cleaved caspase‐3, and cleaved caspase‐9, as well as upregulated Bcl‐2 and p‐ERK expression in vivo and in vitro . Thus, our data suggest that levosimendan reduces mortality and AKI following CA and CPR via suppression of inflammation and apoptosis, and activation of ERK signaling. Abstract : Acute kidney injury (AKI) is an important morbidity of cardiac arrest (CA). Levosimendan, a nonselective ATP‐sensitive potassium channel (KATP) activator, could alleviate AKI following CA and cardiopulmonary resuscitation (CPR) via suppression of inflammation and apoptosis and activation of ERK signaling.